A review of Cryptosporidium spp. infection in livestock - Raja Abdul Rahman, Raja Nur Rahifah Inani; Md Isa, Muhammad Lokman; Mat Yusof, Afzan (Universiti Teknologi Malaysia, 2017)
Cryptosporidium infection is a major problem in neonatal ruminants. Cryptosporidium is a zoonotic small protozoan parasite (4-6µm) that inhabit microvillus border of epithelium mucosal in many vertebrates including livestock. Cryptosporidium spp. is known as one of the most common water and foodborne diseases. It is a common cause diarrhea in human and animals. This review highlights the occurrence of Cryptosporidium infection livestock particularly in cattle, goats, sheep and buffaloes are explained in this review paper including the clinical and pathological features and the interaction of Cryptosporidium spp. with other enteropathogens. The information about the transmission, epidemiological factors of the infection and economic losses are also discussed in this paper. Cryptosporidium infection is a major problem in livestock as the infection causes neonatal diarrhea syndrome. Cryptosporidium infections in small ruminants may be a source for cryptosporidiosis in human. Since there is a lack of effective drug available to treat cryptosporidiosis, application of proper effective management is a must to prevent the spread of cryptosporidiosis among the livestock.